Analisis Penggunaan Media Pembelajaran Terhadap Hasil Belajar Siswa di SMA Negeri Magepanda: Analisis Penggunaan Media Pembelajaran Terhadap Hasil Belajar Siswa di SMA Negeri Magepanda - Rey Kurnia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze the use of learning media in improving student learning outcomes at Magepanda State High School. This study uses a qualitative method. The data sources for this study are teachers and students at Magepanda State High School. Data collection techniques use interviews and observation, while analysis techniques use descriptive analysis. In addition to interview data, data is also collected using documentation in the form of photos and voice recordings. Learning media helps students understand the material more quickly, increases their enthusiasm, and motivates them to learn actively. After the implementation of learning media, there was a significant increase in student learning outcomes, as indicated by a change in behavior from passive to more active, focused, and enthusiastic. The use of media such as multimedia, videos, and learning applications has been proven to increase student motivation and concentration.